Manufacturing and testing method of composite structure flexible sensor based on laser direct writing

Through laser direct writing technology, liquid metal is injected into flexible sensors to form a rough microstructure, which solves the problem of insufficient stability and sensing range of the sensor during mechanical deformation, and achieves high sensitivity and durability. It is suitable for conformal patches on human surfaces. Hehe virtual reality system control.

CN119164523APending Publication Date: 2024-12-20BEIJING INFORMATION SCI & TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410581480.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing flexible pressure sensors have reduced stability during mechanical bending and stretching, high material cost, complex preparation process, and insufficient sensing range, making it difficult to meet the requirements of conformal fit with the human body or flexible equipment surface.

Method used

Using the microstructure-liquid metal composite structure flexible sensor production method based on laser direct writing, the microflower is injected into liquid metal through femtosecond laser direct writing processing, adjust the laser parameters and leave a rough texture on the PDMS surface, thereby increasing the contact area of ​​liquid metal , combining rough microstructure and liquid metal composite materials to achieve the tensibility and resistance changes of the sensor.

Benefits of technology

Improves sensor sensitivity, response time and stability, maintains contact on curved or uneven surfaces, enhances durability, and is suitable for intuitive control of wearable devices and virtual reality systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119164523A_ABST
    Figure CN119164523A_ABST
Patent Text Reader

Abstract

The invention discloses a manufacturing and testing method of a composite structure flexible sensor based on laser direct writing, and belongs to the field of flexible sensors. According to the invention, through selection of various sensor materials and corresponding microstructure design, the contact relation change of the conductive microstructure is realized; by adopting the manufacturing process of processing the micro-channel through laser direct writing and injecting the liquid metal, direct construction of a three-dimensional circuit can be realized only by using femtosecond laser, and patterning of any complex liquid metal can be realized. By adjusting laser parameters, rough textures are left at the bottom of a channel during PDMS surface processing, and the contact area of liquid metal is increased; the rough microstructure is adopted to provide a larger contact surface area of the rough microstructure and the liquid metal, and the sensitivity of the microstructure-liquid metal composite structure flexible sensor to pressure change is improved; the rough microstructure can be kept in contact with a target even on a bent or uneven surface, so that the accuracy and consistency of the flexible sensor on pressure measurement are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing and testing a flexible sensor of a microstructure-liquid metal composite structure based on laser direct writing, and belongs to the field of flexible sensors. Background Art

[0002] Flexible electronic devices can closely fit with soft, curved, and dynamic biological systems, and play an increasingly important role in human health monitoring and biomedical fields. In the context of epidermal electronics, they can achieve conformal interaction with soft human skin and establish reliable interfaces for electrophysiological sensing and electrical activity stimulation. Applications in wearable electronics, smart textiles, robotics, and biomedical devices have driven the demand for flexible pressure sensors with higher sensitivity, reliability, and durability.

[0003] The composition of flexible electronic devices can vary depending on the specific application, but common components include flexible substrates, conductive materials, and flexible encapsulation layers. Flexible substrates: Made of polymer films that can be bent without breaking, they provide a flexible and durable foundation for electronic components. Conductive materials: Often used as conductive components in flexible devices. Encapsulation layers: To protect electronic components from environmental factors such as moisture and oxygen, flexible material films with barrier properties are used. The combination of these materials and components can create electronic devices that are flexible, lightweight, and adaptable to different shapes. In order to prepare flexible sensors, the selection of flexible conductive materials is inevitably a crucial part. At present, the conductive parts of flexible conductive materials are mainly divided into the following four categories: (1) metal materials (gold, silver, copper, etc.) and their nanomaterials, such as silver nanowires, silver nanosheets, etc.; (2) nanoinorganic materials (graphene, carbon nanotubes, conductive carbon black, etc.); (3) conductive polymers (polyaniline, polypyrrole, polythiophene, etc.); (4) systems such as ionic liquids. Flexible electronic devices are inevitably affected by continuous structural deformations such as mechanical bending and stretching, which usually leads to reduced device stability. These strain sensors usually have a large sensing range and sensitivity coefficient, but these materials are expensive, the preparation process is complex, and the performance is greatly reduced due to the separation of fillers caused by stretching, bending and other operations during use. The repeatability and linearity of their electrical response need to be improved because their core sensing mechanism involves unstable contact relationships: complex slip, friction and adhesion relationships on the contact surface; nonlinear deformation of microstructures; and conversion of contact modes.

[0004] Liquid metal is an emerging material. Since liquid metal is in liquid state at room temperature, it not only has electrical conductivity similar to that of metal, but also has flexible properties that metal does not have. Liquid metal has good self-healing properties. It can reorganize and restore its structure autonomously after being damaged, thus improving the durability and life of flexible and stretchable devices. The liquid metals that are currently being studied more are mercury, sodium or sodium-potassium eutectic, and gallium-based alloys. Mercury is a common liquid metal. However, mercury is highly toxic and volatile. Its vapor can cause poisoning if inhaled by the human body or if the skin comes into contact with mercury-containing salt solutions. Sodium or sodium-potassium eutectic has high thermal conductivity and is used as heat transfer material in nuclear reactors, but it is expensive, reacts violently with water, and is not easy to control. Gallium-based liquid metal (GLM) is an emerging multifunctional material with a melting point close to or below room temperature. It has the electrical conductivity and thermal conductivity of metals, as well as the low viscosity and easy flow characteristics of fluids.

[0005] Gallium-based liquid metals have high surface tension that enables them to self-heal and maintain their spherical shape, making them suitable for applications where the material needs to withstand deformation or mechanical stress, while also affecting their capillary behavior, allowing them to move against gravity through narrow channels or between surfaces. This property has applications in microfluidics, where precise control of liquid movement is critical.

[0006] Direct or indirect 3D printing methods are usually used to manufacture pressure sensors with various liquid metal (LM) microchannels to form consistent and adjustable conductive pathways. Processes such as photolithography, soft lithography, and roll-to-roll manufacturing enable the manufacture of sensors with precise features on flexible materials such as polymers and elastomers. The current processing methods for making microfluidic models still have limitations in model design, production speed, production cost, and equipment requirements. When using the 3D printing method, only specific plastics with certain mechanical properties can be used for 3D printing production, and weak interlayer adhesion can cause leakage or delamination of microfluidic channels; the template method cannot easily achieve highly complex designs, involves multiple steps in the manufacturing process, and consumes a lot of time.

[0007] Laser direct writing (LDW) is a versatile manufacturing technology that uses a focused laser beam to create patterns, structures, or functional devices directly on a substrate. LDW enables patterning and structuring of materials with micron-level accuracy. The focused laser beam can precisely control the size and geometry of the written features, making it suitable for applications that require fine details. Unlike traditional lithography techniques that require masks or templates, LDW is a maskless process. This allows for rapid prototyping and fabrication of custom patterns without the need for expensive or time-consuming mask manufacturing steps. And LDW can write patterns or structures directly on a variety of substrates, including polymers, metals, ceramics, semiconductors, and even biomaterials. This versatility makes LDW suitable for a wide range of applications in different industries.

[0008] Polydimethylsiloxane (PDMS) films have a relatively low absorption coefficient in the visible and near-infrared spectral ranges. Therefore, high-energy lasers, such as pulsed lasers operating in the infrared or ultraviolet range, are usually used to provide sufficient energy for the carbonization process. Under certain temperature and pressure conditions induced by the laser, PDMS decomposes to form carbon-rich substances. These carbonaceous substances can undergo rearrangement and condensation reactions, resulting in the formation of graphitic carbon structures on the surface.

[0009] Traditional metal or semiconductor-based strain gauges cannot meet the basic requirements of conformal adhesion to the surface of the human body or flexible devices, and the sensing range is smaller than actual needs. Summary of the invention

[0010] The purpose of the present invention is to provide a method for manufacturing and testing a composite structure flexible sensor based on laser direct writing, and to manufacture a microstructure-liquid metal composite structure flexible sensor based on laser direct writing and contact resistance mechanism, that is, to realize the change of contact relationship of conductive microstructure (change from contact to separation, or change of distance relationship between seepage effect and tunnel effect) through selection of various sensor materials and corresponding microstructure design, so as to form the stretchability and resistance change of the sensor; to adopt the manufacturing process of laser direct writing processing microchannel injection of liquid metal, to realize the complex patterning of liquid metal in flexible silicone elastomer. At the same time, the laser parameters are adjusted to leave a rough texture at the bottom of the channel when processing the PDMS surface, increase the contact area of ​​the liquid metal, and be more conducive to improving the performance of the sensor such as high sensitivity, response time and stability during pressure testing.

[0011] The purpose of the present invention is achieved through the following technical solutions.

[0012] The present invention discloses a method for manufacturing and testing a composite structure flexible sensor based on laser direct writing, comprising the following steps:

[0013] Step 1: Based on the processing optical path module and the processing imaging module, the polydimethylsiloxane film PDMS is patterned by laser to prepare a microchannel. The polydimethylsiloxane film PDMS refers to a PDMS with a thickness ranging from 100 to 500 microns.

[0014] The processing optical path module adopts femtosecond laser direct writing processing optical path, which is mainly composed of beam expander, optical isolator, reflector, focusing objective lens and aperture. The processing optical path module adopts femtosecond laser direct writing processing optical path to adjust laser power, focus and determine the position of the optical path. The modulated laser will be focused onto the processing translation stage through the objective lens; by using focusing objective lenses with different numerical apertures for processing, nanostructures with different powers can be processed, thereby realizing arbitrarily complex liquid metal patterning.

[0015] The processing imaging module is mainly composed of a dichroic mirror, an illumination source, a reflector, and a CCD. The illumination source uses an LED light source to provide the light intensity for processing, and the CCD converts the received light signal into a digital signal to monitor the sample processing in real time.

[0016] Step 2: Use a syringe to place a drop of liquid metal in the groove on the PDMS patterned in step 1, and cover the film with a layer of PDMS, squeeze the liquid metal into the microchannel, and after the liquid metal completely fills the microchannel, plug the vents with glue to obtain a microstructure-liquid metal composite structure.

[0017] Liquid metal quickly forms a self-limiting thin oxide layer when exposed to oxygen, and the thin oxide layer refers to an oxide layer with a thickness of 30 to 60 nanometers. The thin oxide layer makes the liquid metal exhibit elastic properties. When the liquid metal and the thin oxide layer experience critical surface stress to destroy the oxide, the liquid metal can flow. By opening vents in the upper PDMS film to discharge the air in the liquid metal, the liquid metal will not flow back from the microchannel after the pressure is removed, avoiding leakage or stratification of complex channels caused by direct injection of liquid metal; after the liquid metal is completely filled into the microchannel, the vents are blocked with glue to obtain a microstructure-liquid metal composite structure.

[0018] The microstructure roughness ranges from 50 to 100 nanometers.

[0019] The rough microstructure at the bottom of the microchannel increases the contact surface area between PDMS and liquid metal, improving the sensitivity of the flexible sensor to pressure changes. The flexible sensor uses the rough microstructure to maintain contact with the target even on curved or uneven surfaces, thereby improving the accuracy and consistency of the flexible sensor's pressure measurement. The use of rough microstructures can distribute stress more evenly and reduce local damage or wear over time; in addition, the flexibility and elasticity of the liquid metal composite material enable the flexible sensor to withstand repeated bending and stretching without significant degradation, thereby enhancing the durability of the sensor.

[0020] Step 3: Insert the wires into both ends of the microfluidic channel that has been injected with liquid metal, apply silicone rubber adhesive to the wire connection and let it stand for more than 2 hours to ensure that the adhesive is cured to achieve the seal between the wire and the PDMS film, and obtain a microstructure-liquid metal composite structure flexible sensor.

[0021] Step 4: The external pressure of the flexible testing device is applied to the surface of the PDMS material to cause deformation, thereby causing a change in the cross-sectional area of ​​the micropores. According to Ohm's law R=ρL / S, as the applied pressure changes, the resistance of the internal liquid metal changes accordingly. The resistance change is converted into an electrical signal output through the measurement circuit, thereby converting the external force applied by the flexible testing device into an electrical signal, realizing the pressure test of the microstructure-liquid metal composite structure flexible sensor. ρ is the resistivity of the material made of the resistor, L is the wire length of the resistor, S is the wire cross-sectional area of ​​the resistor, and R is the resistance value.

[0022] Preferably, the microstructure-liquid metal composite structure flexible sensor prepared in step 3 is integrated into a wearable device, and the sensor is attached to the wrist or finger. As the wrist or finger bends differently, the resistance changes accordingly. The change in resistance value is measured using a flexible sensor, and hand movements and gestures are captured based on the change in resistance value, thereby achieving intuitive control of electronic devices, virtual reality systems, and augmented reality applications.

[0023] Beneficial effects:

[0024] 1. Compared with the existing direct or indirect 3D printing methods for manufacturing pressure sensors with various liquid metal LM microchannels, the present invention discloses a composite structure flexible sensor manufacturing and testing method based on laser direct writing, which adopts the manufacturing process of laser direct writing microchannel injection of liquid metal. It can realize the direct construction of three-dimensional circuits using only femtosecond laser, and can realize arbitrarily complex liquid metal patterning, which is convenient for using flexible and stretchable electronic devices to construct three-dimensional conductive paths.

[0025] 2. The present invention discloses a method for making and testing a composite structure flexible sensor based on laser direct writing. By adjusting the laser parameters, a rough texture is left at the bottom of the channel during PDMS surface processing, thereby increasing the contact area of ​​the liquid metal, so that the composite structure flexible sensor can more effectively detect subtle changes in pressure and improve the sensitivity of the microstructure-liquid metal composite structure flexible sensor to pressure changes. The flexible sensor uses a rough microstructure to maintain contact with the target even on a curved or uneven surface, thereby improving the accuracy and consistency of the flexible sensor's pressure measurement.

[0026] 3. The present invention discloses a method for manufacturing and testing a composite structure flexible sensor based on laser direct writing, which combines a rough microstructure and a liquid metal composite material to enhance the durability of the sensor. The rough surface can distribute stress more evenly, reducing the possibility of local damage or wear over time. In addition, liquid metal composite materials are generally highly flexible and elastic, allowing the sensor to withstand repeated bending and stretching without significant degradation.

[0027] 4. The present invention discloses a method for manufacturing and testing a composite structure flexible sensor based on laser direct writing. The manufactured flexible sensor of microstructure-liquid metal composite structure has the characteristics of high sensitivity, short response time, good stability, etc. It is integrated into a wearable device and the sensor is attached to the wrist or finger. As the wrist or finger bends, the resistance changes accordingly. The flexible sensor is used to measure the change in resistance value, and the hand movements and gestures are captured according to the change in resistance value, thereby realizing intuitive control of electronic devices, virtual reality systems, and augmented reality applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of a flexible sensor based on laser direct writing microstructure-liquid metal composite structure.

[0029] Figure 2 This is the SEM image of the rough surface of PDMS.

[0030] Figure 3 Test the resistance change of the flexible sensor when the wrist moves.

[0031] Figure 4 Resistance change during the repeatability test of the flexible sensor. DETAILED DESCRIPTION

[0032] In order to better illustrate the purpose and advantages of the present invention, the invention is further described below with reference to the accompanying drawings and examples.

[0033] Embodiment 1:

[0034] like Figure 1 As shown (the accompanying figure has been modified), the present embodiment discloses a method for manufacturing and testing a composite structure flexible sensor based on laser direct writing, and the specific implementation steps are as follows:

[0035] Step 1: After building the laser platform, import the drawn template diagram into the laser processing software, and design the shape of the solid electrode into a serpentine pattern that can adapt to large mechanical deformations, including strains applied to the electrode. At the same time, the square grooves at both ends are used to connect the wires. The use of laser ablation to remove PDMS (polydimethylsiloxane) is affected by several key parameters that affect the efficiency, quality and characteristics of the removal process. Using the parameters of 10× objective lens, 200mw power, 10kHz repetition rate, and 5mm / s scanning speed, a femtosecond laser is used to directly write on the surface of the polydimethylsiloxane film (PDMS) to prepare a microfluidic channel. It can be seen that the bottom surface of the microfluidic channel removed by laser has obvious roughness ( Figure 2 ). The microstructure roughness ranges from 50 to 100 nanometers.

[0036] Laser pulse duration: The duration of each laser pulse (often referred to as pulse width or pulse duration) affects the energy delivered to the PDMS surface. Shorter pulse durations result in higher peak power density and can lead to more precise and localized ablation. However, pulses that are too short may also cause thermal damage to surrounding materials. Longer pulse durations may be suitable for bulk removal, but may result in an increased heat-affected zone.

[0037] Laser beam spot size: The size and shape of the laser beam spot affects the spatial resolution and accuracy of PDMS removal. Smaller spot sizes produce finer feature resolution but may require longer processing times for large area removal. Larger spot sizes can speed up the removal process but may sacrifice spatial resolution.

[0038] Laser Pulse Repetition Frequency: The repetition rate of the laser pulses affects the total energy delivered to the PDMS surface over time. Higher repetition rates can increase overall removal rates, but may also result in greater heat accumulation and thermal effects. Lower repetition rates may be preferred for applications that require precise control of the ablation process.

[0039] Scanning speed: The speed at which the laser beam is scanned across the PDMS surface determines the dwell time and heat accumulation at each location. Higher scanning speeds can reduce dwell time and minimize thermal effects, but may also limit the depth of ablation. Lower scanning speeds can deliver more energy per unit area, resulting in deeper ablation, but may increase the risk of thermal damage.

[0040] Laser energy is absorbed by the PDMS surface, resulting in rapid heating. PDMS is a soft elastomer with relatively low melting and degradation temperatures. Laser ablation causes localized heating, resulting in melting and resolidification, which can create irregularities on the surface. The choice of laser wavelength, power, pulse duration, and repetition rate can all affect the material removal process, resulting in more significant surface roughness.

[0041] Step 2: Use a syringe to place a drop of liquid metal in the groove on the PDMS and cover the film with a layer of PDMS, then squeeze the liquid metal into the template.

[0042] Liquid metals quickly form a self-limiting thin oxide layer when exposed to oxygen. Although the oxide skin makes liquid metals behave like an elastic material, once they experience a critical surface stress to destroy the oxide, liquid metals can flow easily. Since positive pressure is required, direct injection may cause leakage or delamination of complex channels. Therefore, a tiny vent is needed in the upper PDMS film to discharge the air in the device, so that the liquid metal will not flow back from the microchannel after the pressure is removed. After the liquid metal is completely filled into the microchannel, the vent is blocked with glue.

[0043] Step 3: Insert the wires into both ends of the channel that has been injected with liquid metal, use a multimeter to measure the circuit, ensure that the wires are in full contact with the LM storage area, apply silicone rubber adhesive to the wire connections and let it stand for more than 2 hours to ensure that the adhesive is cured to achieve sealing.

[0044] Step 4: Use a flexible test device to measure the resistance change of the sensor when the external pressure changes. The external pressure applied to the surface of the PDMS material causes deformation, which causes the cross-sectional area of ​​the microfluidic pores to change. According to Ohm's law R = ρL / S, it can be concluded that as the applied pressure changes, the resistance of the internal liquid metal changes accordingly. The resistance change is converted into an electrical signal output through the measurement circuit, thereby converting the applied external force into an electrical signal.

[0045] Flexible sensors integrated into wearable devices can capture hand movements and gestures, enabling intuitive control of electronic devices, virtual reality systems, and augmented reality applications. This technology enhances user interaction and expands the capabilities of wearable devices beyond traditional input methods.

[0046] The sensor is fixed on the wrist to monitor the bending of the fingers. As the bending angle increases, the detected sensor response also increases (e.g. Figure 3 As shown in Figure 2 ). And when the wrist is raised, the resistance value returns to the initial state. Therefore, the sensor can be used to monitor joint movement at different bending angles. When the sensor is subjected to multiple cycles of repetitive pressure testing under a given pressure, the resistance change remains basically unchanged, indicating that the sensor response is stable (as shown in Figure 2 ). Figure 4 ). At the same time, the feasibility of using femtosecond laser to prepare flexible pressure sensors in the present invention is also verified.

[0047] The specific description above further illustrates the purpose, technical solutions and beneficial effects of the invention in detail. It should be understood that the above is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for manufacturing and testing a composite structure flexible sensor based on laser direct writing, characterized in that: The following steps are included: Step 1: Based on the processing optical path module and the processing imaging module, the polydimethylsiloxane film PDMS is patterned by laser to prepare a microchannel; the polydimethylsiloxane film PDMS refers to a PDMS with a thickness ranging from 100 to 500 microns; The processing optical path module adopts femtosecond laser direct writing processing optical path, which is mainly composed of a beam expander, an optical isolator, a reflector, a focusing objective lens, and an aperture; the processing optical path module adopts femtosecond laser direct writing processing optical path to adjust the laser power, focus, and determine the position of the optical path. The modulated laser will be focused onto the processing translation stage through the objective lens; by using focusing objective lenses with different numerical apertures for processing, nanostructures with different powers can be processed, thereby realizing arbitrarily complex liquid metal patterning; The processing imaging module is mainly composed of a dichroic mirror, an illumination light source, a reflector, and a CCD. The illumination light source uses an LED light source to provide the light intensity for processing, and the CCD converts the received light signal into a digital signal to monitor the sample processing in real time. Step 2: Use a syringe to place a liquid metal droplet on the groove of the PDMS patterned in step 1, and cover a layer of PDMS on the film, squeeze the liquid metal into the microchannel, and after the liquid metal is completely filled into the microchannel, plug the vent with glue to obtain a microstructure-liquid metal composite structure; Step 3: Insert the wires into both ends of the microfluidic channel that has been injected with liquid metal, fully apply silicone rubber adhesive to the wire connection and let it stand for more than 2 hours to ensure that the adhesive is cured to achieve the seal between the wire and the PDMS film, and obtain a microstructure-liquid metal composite structure flexible sensor; Step 4: The external pressure applied by the flexible testing device is applied to the surface of the PDMS material, causing deformation, thereby causing a change in the cross-sectional area of ​​the micropores; according to Ohm's law R=ρL / S, it is concluded that as the applied pressure changes, the resistance of the internal liquid metal changes accordingly, and the resistance change is converted into an electrical signal output through the measuring circuit, thereby converting the external force applied by the flexible testing device into an electrical signal, thereby converting the external force applied by the flexible testing device into an electrical signal, thereby realizing the pressure test of the microstructure-liquid metal composite structure flexible sensor; ρ is the resistivity of the material making the resistor, L is the wire length of the resistor, S is the wire cross-sectional area of ​​the resistor, and R is the resistance value.

2. The method for manufacturing and testing a composite structure flexible sensor based on laser direct writing as claimed in claim 1, characterized in that: In step 2, the liquid metal quickly forms a self-limiting thin oxide layer when exposed to oxygen, and the thin oxide layer refers to an oxide layer with a thickness of 30 to 60 nanometers; the thin oxide layer makes the liquid metal exhibit elastic properties, and when the liquid metal and the thin oxide layer experience critical surface stress to destroy the oxide, the liquid metal can flow; by opening vents in the upper PDMS film to discharge the air in the liquid metal, the liquid metal will not flow back from the microchannel after the pressure is removed; after the liquid metal is completely filled into the microchannel, the vents are blocked with glue to obtain a microstructure-liquid metal composite structure.

3. The method for manufacturing and testing a composite structure flexible sensor based on laser direct writing as claimed in claim 2, characterized in that: In step 2, the microstructure roughness ranges from 50 to 100 nanometers; The rough microstructure at the bottom of the microchannel increases the contact surface area between PDMS and liquid metal, thereby improving the sensitivity of the microstructure-liquid metal composite flexible sensor to pressure changes; the flexible sensor utilizes the rough microstructure to maintain contact with the target even on curved or uneven surfaces, thereby improving the accuracy and consistency of pressure measurement by the flexible sensor; the use of a rough microstructure can more evenly distribute stress and reduce local damage or wear over time; in addition, the flexibility and elasticity of the liquid metal composite material enable the flexible sensor to withstand repeated bending and stretching without significant degradation.

4. A method for manufacturing and testing a composite structure flexible sensor based on laser direct writing as claimed in claim 1, 2 or 3, characterized in that: The microstructure-liquid metal composite structure flexible sensor produced in step three is integrated into the wearable device. The sensor is attached to the wrist or finger. As the wrist or finger is bent, the resistance changes accordingly. Flexible sensors are used to measure changes in resistance and capture hand movements and gestures based on the changes in resistance, thereby achieving intuitive control of electronic devices, virtual reality systems, and augmented reality applications.

Citation Information

Cited By

  • Multidirectional flexible sensor and preparation method thereof

    CN119779364A